Improving Triage Accuracy in First Responders: Measurement of Short Structured Protocols to Improve Identification of Salient Triage Features. Issue 2 (9th July 2019) - Loth, Sarah; Cote, Alanna C.; Shaafi Kabiri, Nina; Bhangu, Jaspreet S.; Zumwalt, Ann; Moss, Mark; Thomas, Kevin
Abstract : Gaze tracking is used in biomedical teaching for situations requiring the assessment of complex visual data. We employed gaze tracking techniques to examine an adapted training protocol using simple triage and rapid treatment (START) triage principles. This study utilized a case‐control design. Both groups were presented with a series of computer images, each corresponding to four levels of injury severity. Subsequently, the experimental group underwent training using the START triage program while the control group underwent training regarding patient transportation. Participants who underwent training with the START protocol fixated upon salient features significantly earlier post‐training as evidenced by decreased post‐training entry time (ms). 1376.35 (1665.69) ( p = .02, 95% confidence interval [CI] [318.02–2434.68]); circulation: 1986.57 (2268.38) ( p = .01, 95% CI [545.31–3427.84]). Those who underwent training only on patient transport and not on the adapted START triage protocol demonstrated no statistically significant between‐session gaze measurement. Subjects who underwent START triage training significantly improved in their first fixation entry time, indicating a faster recognition of salient triage features. We have shown the effectiveness of a short, directed triage training tool in improving the recognition of triage features.